2014
DOI: 10.1186/2193-1801-3-250
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of dose measurement other than the radiation protection during the radiographic examination

Abstract: ObjectivesThe study measured the dose on body regions that were not shielded to protect from radiation exposure during the general procedure, with the goal of providing basic radiation dose data for radiological technologists who perform the radiographic examination.Materials and methodsShooting parts with the phantom were similar to human tissues using general shooting equipment in the general examination room. The scattered rays were measured with the ion chamber. The hand received the highest average radiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…In previous studies, it has been shown that each part of the body is exposed to radiation at different levels depending on the type of radiation, and the necessity of using the right protective equipment was emphasized. [11] Several measures have been reported to protect against the harmful effects of ionizing radiation. Equipment such as lead goggles, thyroid protectors, lead aprons, etc., is very important in preventing radiation exposure, particularly in fluoroscopic examinations where workers are exposed to direct radiation.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, it has been shown that each part of the body is exposed to radiation at different levels depending on the type of radiation, and the necessity of using the right protective equipment was emphasized. [11] Several measures have been reported to protect against the harmful effects of ionizing radiation. Equipment such as lead goggles, thyroid protectors, lead aprons, etc., is very important in preventing radiation exposure, particularly in fluoroscopic examinations where workers are exposed to direct radiation.…”
Section: Discussionmentioning
confidence: 99%
“…The radiation dose received by the pediatric patient's companion, especially on thoracic examination, was much lower than the maximum permissible dose threshold by the Indonesian Nuclear Energy Regulatory Agency, Regulation Number 4 the year 2020 on Radiation Safety in The Use of X-Ray Machine in Diagnostic Interventional Radiology, even without the use of radiation protection equipment. These studies' results were compared with Kim et al's work for xray irradiation doses between 0.52 ± 0.08 to 46.74 ± 11.22 µSv [12]. Based on research conducted by Farzanegan et al in 2020 in five teaching hospitals, out of 26 examination samples, only 1 radiography examination using radiation protection equipment [13].…”
Section: Relationship Between Variations In Exposure Factors To Radia...mentioning
confidence: 98%